ERROR 404 – Sleep not found - George L. Muntingh; Michelle Viljoen (South African Family Practice)
Insomnia is perhaps the most common type of sleep disorder in the family medicine population. It is best described as a persistent difficulty initiating or maintaining sleep, or a report of non-restorative sleep, accompanied by related daytime impairment. There is increasing evidence of a strong association between insomnia and various medical and psychiatric comorbidities. Diagnosis of insomnia and treatment planning rely on a thorough sleep history to address contributing and precipitating factors as well as maladaptive behaviours resulting in poor sleep. Cognitive behavioural therapy for insomnia (CBT-I) is the mainstay of treatment and is a safe and effective approach. The key challenge of CBT-I is the lack of clinicians to implement it. The newer generation nonbenzodiazepines (e.g. zolpidem) are used as first-line pharmacotherapy for chronic insomnia. Newer drugs active on targets other than the gamma-aminobutyric acid receptor are now available, but clear treatment guidelines are needed.